Mr. dickens and his carol ebook A novel. - Silva, Samantha (2017)
"CHARMING...I READ IT IN A COUPLE OF EBULLIENT, CHRISTMASSY GULPS." —Anthony Doerr, #1 New York Times bestselling author of All The Light We Cannot See "GRACED BY THE GHOSTLY PRESENCE OF MR. DICKENS HIMSELF...PROMISES TO PUT YOU IN THE HOLIDAY SPIRIT." — USA Today A beloved, irresistible novel that reimagines the story behind Charles Dickens' Christmas classic Charles Dickens is not feeling the Christmas spirit. His newest book is an utter flop, the critics have turned against him, relatives near and far hound him for money. While his wife plans a lavish holiday party for their ever-expanding family and circle of friends, Dickens has visions of the poor house. But when his publishers try to blackmail him into writing a Christmas book to save them all from financial ruin, he refuses. And a serious bout of writer's block sets in. Frazzled and filled with self-doubt, Dickens seeks solace in his great palace of thinking, the city of London itself. On one of his long night walks, in a once-beloved square, he meets the mysterious Eleanor Lovejoy, who might be just the muse he needs. As Dickens' deadlines close in, Eleanor propels him on a Scrooge-like journey that tests everything he believes about generosity, friendship, ambition, and love. The story he writes will change Christmas forever.